Educating patients suffering from re-acutisation of chronic bronchitis. A pilot support project within Intermediate Care (Italian Journal of Public Health, 2006)
Background: Chronic Obstructive Pulmonary Disease (COPD) represents one of the main causes ofhospitalization, disability and mortality worldwide; it is predicted that by the year 2020 it will become thethird leading cause of death and the fifth leading cause of disability in industrialized countries.An educational programme has been proposed to allow the COPD patient to prevent or to deal with a re-acutisation.Methods: The project involved 50 patients with a diagnosis of moderate or severe COPD. The educationprogram included information relating to disease process, proper use of medication, energy conservationmethods, and the filling in of the Saint George’s Respiratory Questionnaire (SGRQ), the Zung Self-RatingDepression Scale (ZSDS) and the State Trait Anxiety Inventory (STAI). Sociodemographic factors,assessment of living arrangements, social and family conditions were also collected. One year later the samequestionnaires and learning assessment tests were re-administered.Results: The mean age of the participants was 69.7±10.4 years with a mean low income and a limited degreeof education. Following the educational program, an improvement of quality of life emerged consequent tothe awareness of all of the forms of support provided for the pathology and socio-economic conditions. Theability to manage their therapy and their activities of daily living have improved. The mean total score onSGRQ was 78.07±7.2 pre-program and 73.12±7.2 post-program; 52% of the patients are now within normalparameters compared to the initial 30% suffering from depression syndrome, furthermore the mean anxietyvalue decreased from 59.54 ± 8.6 to 54.54±7.8. The number of hospital admissions and the number ofsmokers were also halved.Conclusion: The improvements obtained after conducting all of the educational sessions are significant. Thehigh value of the mean total score on SGRQ suggests overall poor health among patients affected bymoderate/ severe COPD and according to other studies this population is inclined to anxiety and depression.The role of the social worker was very important because the explanation of the appropriate laws has leadto the recognition of their disability status and therefore access to established benefits. The decrease inhospitalization has brought about an economic benefit for the educational program but further studiesshould be carried out on more patients over longer periods of time
Keywords: chronic obstructive pulmonary disease (COPD); patient educatio; quality of life